2019
DOI: 10.1002/est2.53
|View full text |Cite
|
Sign up to set email alerts
|

Composite material for high‐temperature thermochemical energy storage using calcium hydroxide and ceramic foam

Abstract: Thermochemical energy storage using a calcium oxide/calcium hydroxide/water (CaO/Ca(OH)2/H2O) reaction system is a promising technology for thermal energy storage at high‐temperatures (400°C‐600°C). The purpose of this study is to develop a practical composite material by enhancing heat transfer through the reaction bed and mitigating problems of pure CaO/Ca(OH)2 materials, such as formation of centimeter‐scale agglomerates and change in the bulk volume during repetitive reactions. The present study focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Lab-scale experiments were performed in an indirectly heated cylindrical fixed bed reactor with a height of 70 mm and an inner diameter of 48 mm, as depicted in Figure 1a. Details of the reactor are described by Funayama et al [34,35]. The reactor is placed in a reaction chamber to allow for pressure variations.…”
Section: Lab-scale Experimentsmentioning
confidence: 99%
“…Lab-scale experiments were performed in an indirectly heated cylindrical fixed bed reactor with a height of 70 mm and an inner diameter of 48 mm, as depicted in Figure 1a. Details of the reactor are described by Funayama et al [34,35]. The reactor is placed in a reaction chamber to allow for pressure variations.…”
Section: Lab-scale Experimentsmentioning
confidence: 99%
“…Under experimental conditions, the highest temperature reached was 475 • C. In fact, the study underlines the unevenness of the heat release rate and the poor thermal conductivity as main issues. To address the improvement of heat transfer through CaO/Ca(OH) 2 in a packed bed reactor, a composite material using silicon carbide/silicon (SiC/Si) foam to support CaO/Ca(OH) 2 in its pores (400 µm) was investigated [17]. Over ten cycles, the composite material retained a high reactivity and good stability of the bulk volume during dehydration/hydration reactions.…”
Section: Tces Systems Based On Hydroxidesmentioning
confidence: 99%
“…Although the additive (Al 2 O 3 ) enhanced the cyclic stability, the heat storage capacity of the system was lost. Funayama et al examined its thermochemical properties in a cylindrically packed bed of Ca(OH) 2 pellets 23 and composite materials, 24 and concluded that the composite material showed 1.4 times volumetric heat output rate for first 5 minutes compared with pure pellets. It has also been reported that CaO/Ca(OH) 2 exhibited low cyclic stability during the heat storage‐and‐release operations due to particle agglomeration 25,26 and sintering, 27 which is a drawback.…”
Section: Introductionmentioning
confidence: 99%